Pendampingan Optimalisasi Layanan Administrasi Online Berbasis Teknologi Informasi di Gampong Jawa Lama - Zahara, Ana; Angreni, Dyah Kuntorini Dwi; Farida, Ratna; Oktaviajianti, Firda; Syahputra, Haris; Saifuddin, Imam; Hanum, Mulyatun; Ramadhan, Jehan; Andriansyah, Andriansyah; Maulana, Fazil; Doni, Dona; Nanda P.S, Josua (Jurnal Solusi Masyarakat (JSM), 2024)
Administrative services are a basic need for society. However, its implementation is still not practical and simple, resulting in effects that can impact other sectors such as the economy. The demographic condition of Gampong Jawa Lama shows that there is no time efficiency which will result in many losses. Apart from that, the absorption of existing village funds shows that the use of paper for administration is still very large which is not in accordance with point 13 of the Sustainable Development Goals, coupled with the impact of the pandemic which has worsened the situation by implementing various restrictions on sectors of society. It is urgent to find a solution that facilitates the community in the administrative sector and Gampong Jawa Lama needs a solution to facilitate the administrative process in terms of delivery distribution and management by village officials to create a minimum system that is effective, efficient and interacts directly. Based on the needs and conditions of Gampong Jawa Lama Village, the online administration solution, namely "Smart Village: Empowering Gampong Jawa Lama through an Intelligent Information System for Online Application-Based Community Administration Services", is an application that can accommodate administrative processes at the village level using the Android system.